Lived Experiences of Head Campers in Summer Camp - Bontuyan, Jessie Limutan; Judaya, Gerbie Rivera; Tero, Alona Padayogdog; Del Castillo, Flordeliza Dayday; Telebangco, Lucel Abucay (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Summer camps have proven effective in providing opportunities for social contact, personal development, and the improvement of the problem-solving and critical-thinking abilities of the students. However, significant findings about head campers’ lived experiences in the field are scarce, especially in the Philippine context. To provide a groundwork of the phenomenon, this study delved into the head campers' lived experiences in preparation and implementation phases using the descriptive phenomenology of Husserl. At the same time, Colaizzi’s seven-step method was used in thematic analysis. Individual guided interviews were utilized to gather participants’ responses. Nine head campers who were active participants from the beginning up to the end of the program served as the participants of the study. Based on the participants’ narratives, the following themes were generated: a) preparation phase: triumphs in camaraderie, teachers are willing to learn new subject matter, time constraints in preparing the resources, and no ample time to review new subject matter; b) implementation phase: develop students’ positive learning behavior, develop students’ thinking skills, Students unable to master the fundamental knowledge, and teachers are struggling to integrate higher order thinking skills. The findings implied that despite the sector and participants’ efforts to make the program successful, there were still untoward instances that are beyond the program’s expectations. Therefore, mentoring sessions and feed-backing activities all throughout the implementation must be strengthened and closely monitored by higher authorities so they can provide immediate and practical assistance for the head campers.